2021
DOI: 10.1039/d1ta02718b
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the enhanced catalytic activity of high entropy alloys: from theory to experiment

Abstract: High-entropy alloys (HEAs) have evolved to be one of the most popular materials in the last decade. Their unique configuration and attractive properties make HEAs one of the most promising...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 152 publications
0
45
0
Order By: Relevance
“…17,19 In HEAs, the sufficiently high thermal energy of a multimetal solid solution ensures that each constituent element occupies a random position in the final crystal structure. 12 Unlike traditional alloys, HEA assimilates four core intrinsic effects, namely, (i) high-entropy effect (promotion of mutual solubility), (ii) cocktail effect (multielemental character at the atomic level, which is expected to offer a variety of active sites and thus the continuous distribution of adsorption energies), (iii) sluggish diffusion (suppression of intermetallic-phase segregation, which further imparts excellent structural thermal/chemical stability), and (iv) lattice distortion (atomic size mismatch causes severe lattice strain that shifts the overall d-band center of the alloy and thus has potential to modify the physicochemical properties). 12,13,17 Inspired by these material features, HEAs have been envisioned as a promising solution to many problems, especially in catalysis where efficacy and stability are much-needed traits.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…17,19 In HEAs, the sufficiently high thermal energy of a multimetal solid solution ensures that each constituent element occupies a random position in the final crystal structure. 12 Unlike traditional alloys, HEA assimilates four core intrinsic effects, namely, (i) high-entropy effect (promotion of mutual solubility), (ii) cocktail effect (multielemental character at the atomic level, which is expected to offer a variety of active sites and thus the continuous distribution of adsorption energies), (iii) sluggish diffusion (suppression of intermetallic-phase segregation, which further imparts excellent structural thermal/chemical stability), and (iv) lattice distortion (atomic size mismatch causes severe lattice strain that shifts the overall d-band center of the alloy and thus has potential to modify the physicochemical properties). 12,13,17 Inspired by these material features, HEAs have been envisioned as a promising solution to many problems, especially in catalysis where efficacy and stability are much-needed traits.…”
Section: ■ Introductionmentioning
confidence: 99%
“…12 Unlike traditional alloys, HEA assimilates four core intrinsic effects, namely, (i) high-entropy effect (promotion of mutual solubility), (ii) cocktail effect (multielemental character at the atomic level, which is expected to offer a variety of active sites and thus the continuous distribution of adsorption energies), (iii) sluggish diffusion (suppression of intermetallic-phase segregation, which further imparts excellent structural thermal/chemical stability), and (iv) lattice distortion (atomic size mismatch causes severe lattice strain that shifts the overall d-band center of the alloy and thus has potential to modify the physicochemical properties). 12,13,17 Inspired by these material features, HEAs have been envisioned as a promising solution to many problems, especially in catalysis where efficacy and stability are much-needed traits. 12,14 However, a facile and user-friendly design for the development of nanostructured HEAs is the foundation for their swift and favorable adoption in heterogeneous catalysis, energy storage, and environmental redemption, though a challenging task to accomplish.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the Al, Co and Ni elements are cytotoxic and may induce apoptosis. Todai et al [9,10] prepared a series of titanium high entropy alloys (TiZrNbTaMo, TiZrNbTaHf) for bone repair using alloying elements without cytotoxicity to humans, and their mechanical properties and biocompatibility are better than 316SS alloy and pure Ti alloy. Yuan et al [11,12] designed and prepared 26 kinds of Ta x Nb x HfZrTi high entropy alloys, which showed that the elastic modulus of high entropy alloy with BCC structure is low and suitable for implantation materials.…”
Section: Introductionmentioning
confidence: 99%